Job Design and Collaborative Human Resource Management from a Tetrapreneur Perspective: BPJPH's Strategy for Addressing Halal Certification Challenges - Isnaeni Gelda Prasetianti; P.L. Rika Fatimah (Halal Center ITS, 2026)
Halal certification in Indonesia plays a strategic role in protecting Muslim consumers and enhancing the competitiveness of the national halal industry. The Halal Product Assurance Agency (BPJPH) administers the certification system; however, its implementation faces challenges related to limited human resources, suboptimal job design, and fragmented inter-institutional coordination. This study analyzes how integrating job design strategies with the Tetrapreneur model can strengthen halal certification governance in BPJPH. This research employs a qualitative approach using framework analysis of policy documents, BPJPH organizational structure, and relevant academic literature. The findings indicate that aligning job design strategies with the Tetrapreneur dimensions can improve institutional coordination, strengthen quality assurance mechanisms, and support the development of a more integrated halal ecosystem. This study contributes to the literature on halal governance and public sector management by proposing an integrative conceptual framework that links human resource management with entrepreneurial governance to enhance the capacity of halal regulatory institutions.